1996
DOI: 10.1080/135468096396451
|View full text |Cite
|
Sign up to set email alerts
|

Delusions in Schizophrenia: A Phenomenological and Psychological Exploration

Abstract: The psychopathological basis of delusions in schizophrenia is poorly understood. The most enduring of several early theories has suggested a causal link with formal thought disorder, whereas recent approaches have proposed relationships with a variety of cognitive abnormalities. The correlations of delusions with other schizophrenic symptoms and with cognitive functions including semantic memory, executive function, and also probabilistic reasoning bias, were examined in a series of (overlapping) groups of 43-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…It is possible that the decision behaviour we measure in the beads task / fish task (whether it is risky or rational) might be still an interesting causal factor involved in the formation and maintenance of symptoms of psychotic disorders. Nevertheless, it might not be causally related to delusions in particular, but rather associated with other symptoms of psychotic disorders such as negative symptoms [47,48], insight [49] or neurocognitive problems [50] (interestingly, in an exploratory analysis, we found negative symptoms to be associated with JTC, r = − .166, p < .05).…”
Section: Lack Of Associations With Psychopathologymentioning
confidence: 75%
“…It is possible that the decision behaviour we measure in the beads task / fish task (whether it is risky or rational) might be still an interesting causal factor involved in the formation and maintenance of symptoms of psychotic disorders. Nevertheless, it might not be causally related to delusions in particular, but rather associated with other symptoms of psychotic disorders such as negative symptoms [47,48], insight [49] or neurocognitive problems [50] (interestingly, in an exploratory analysis, we found negative symptoms to be associated with JTC, r = − .166, p < .05).…”
Section: Lack Of Associations With Psychopathologymentioning
confidence: 75%
“…Thus, the current findings may appear to show some correspondence with the view of JTC being an epiphenomenal effect of broader cognitive deficits in schizophrenia. These studies (Garety et al, 1991;Menon, Pomarol-Clotet, McCarthy, & McKenna, 2002;Moritz & Woodward, 2005;Mortimer et al, 1996) have found a JTC effect in patients with schizophrenia but without delusions. This suggests that JTC is not a cognitive bias, but rather a cognitive deficit (see Bentall, 1995;David, 1995), and that this deficit alone cannot explain the occurrence of delusions.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, one of the original studies of JTC and delusions found that JTC was less marked in a delusional disorder subgroup relative to the main group of people with schizophrenia (Garety, Hemsley, & Wessely, 1991). It has also been found that there was no correlation between level of delusions and JTC in a group of individuals with schizophrenia (Mortimer et al, 1996). A recent meta-analysis (Fine et al, 2007) suggested that the JTC effect found in deluded schizophrenia groups may not be exclusively related to delusions, and that at least some of the bias may arise from other schizophrenic symptoms or impairments.…”
mentioning
confidence: 99%
“…Many subsequent studies have confirmed this finding (for a review see Garety & Freeman, 2013). However, in much the same way as with theory of mind impairment, these studies have struggled to demonstrate an association with presence or severity of delusions (Dudley et al, 2011; Falcone et al, 2015; Freeman et al, 2014; Garety et al, 2013; Langdon, Ward, & Coltheart, 2010; Lincoln, Ziegler, Mehl, & Rief, 2010; Menon, Pomarol-Clotet, McKenna, & McCarthy, 2006; Moritz & Woodward, 2005; Mortimer et al, 1996; Ochoa et al, 2014; Peters, Thornton, Siksou, Linney, & MacCabe, 2008; So et al, 2012). …”
Section: Theories Of Delusionsmentioning
confidence: 99%